'Both sides now': the meitheal method for professional development in higher education. Issue 1 (1st January 2021) - Brereton, Bernadette
ABSTRACT: In 2017, the participants of a higher education professional development (PD) working group (meitheal) met face-to-face and remotely to examine the National Forum for the Enhancement of Teaching and Learning in Higher Education (NFTL) Framework for Professional Development. Through collaboration and mentorship, members of the meitheal successfully familiarised themselves with the PD framework document and built a community of practice of inter-disciplinary and inter-institutional practitioners. Using a self-study conceptual framework, this article reflects on the work of the meitheal, its establishment and organisation, its influences on the participants and its place in the national PD project. It draws on the shared reflections of the participants and feedback gathered throughout the project, by means of discussion, written reflections, focus groups, audio and video diaries, and NFTL feedback sheets. It draws conclusions and makes recommendations for future professional development projects, drawing on the epistemological, technological and social foundations of self-study theory.